2019
DOI: 10.1186/s12902-019-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Can MiR-503 be used as a marker in diabetic patients with ischemic stroke?

Abstract: Background Some microRNAs are involved in diabetes pathology and some are known to have role in stroke. MiR-503 causes endothelial dysfunction in diabetic patients, predisposing to ischemia. There has been no study evaluating Mir-503 level in diabetic patients with or without ischemic stroke. Methods We designed a cross-sectional study to assess and compare serum level of MiR-503 in 4 groups of diabetic patients with ischemic stroke (I), non-diabetic patients with strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
(56 reference statements)
1
16
0
Order By: Relevance
“… 9 Sheikhbahaei et al reported that miR-503 was stable enough in the blood to be a potential diagnostic marker for ischemic stroke in diabetic patients. 10 The miR-503 in the placenta tissues of patients with gestational diabetes mellitus was significantly up-regulated, and the miR-503 in peripheral blood samples increased, and it was positively correlated with the blood glucose concentration. 11 Yan et al reported that the expression levels of miR-503-5p were significantly associated with diabetes and arterial stenosis.…”
Section: Introductionmentioning
confidence: 94%
“… 9 Sheikhbahaei et al reported that miR-503 was stable enough in the blood to be a potential diagnostic marker for ischemic stroke in diabetic patients. 10 The miR-503 in the placenta tissues of patients with gestational diabetes mellitus was significantly up-regulated, and the miR-503 in peripheral blood samples increased, and it was positively correlated with the blood glucose concentration. 11 Yan et al reported that the expression levels of miR-503-5p were significantly associated with diabetes and arterial stenosis.…”
Section: Introductionmentioning
confidence: 94%
“…In EPCs ( Wen et al, 2018 ), miR-503 suppressed angiogenesis by targeting Apelin. In Diabetes mellitus, miR-503 expression level was significantly higher in ischemic muscles and plasma from patients with limb ischemia than normal control ( Caporali et al, 2011 ), and it is also higher in the plasma of diabetic patients with ischemic stroke than that in non-diabetic patients with stroke or in control individuals ( Sheikhbahaei et al, 2019 ). Overexpression of miR-503 suppressed endothelial cells proliferation, migration and network formation by suppression of its targets, cdc25A (cell division cycle 25 A) and CCNE1 (cyclin E1) under normal culture condition ( Caporali et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-503 is a hyperglycaemia-sensitive miRNA that can be highly expressed in diabetic patients [17]. Besides that, miR-503 was considered as a factor in regulating neuro-damage [18], which suggested it acted as a potential therapeutic target in DPN.…”
Section: Introductionmentioning
confidence: 99%